Boosting BCG with recombinant influenza A virus tuberculosis vaccines increases pulmonary T cell responses but not protection against Mycobacterium tuberculosis infection. - Heni Muflihah (Public Library of Science (PLoS), 2021)
The current Mycobacterium bovis BCG vaccine provides inconsistent protection against pulmonary infection with Mycobacterium tuberculosis. Immunity induced by subcutaneous immunization with BCG wanes and does not promote early recruitment of T cell to the lungs after M. tuberculosis infection. Delivery of Tuberculosis (TB) vaccines to the lungs may increase and prolong immunity at the primary site of M. tuberculosis infection. Pulmonary immunization with recombinant influenza A viruses (rIAVs) expressing an immune-dominant M. tuberculosis CD4+ T cell epitope (PR8-p25 and X31-p25) stimulates protective immunity against lung TB infection. Here, we investigated the potential use of rIAVs to improve the efficacy of BCG using simultaneous immunization (SIM) and prime-boost strategies. SIM with parenteral BCG and intranasal PR8-p25 resulted in equivalent protection to BCG alone against early, acute and chronic M. tuberculosis infection. Boosting BCG with rIAVs increased the frequency of IFN-γ-secreting specific T cells (p<0.001) and polyfunctional CD4+ T cells (p<0.05) in the lungs compared to the BCG alone, however, this did not result in a significant increase in protection against M. tuberculosis compared to BCG alone. Therefore, sequential pulmonary immunization with these rIAVs after BCG increased M. tuberculosis-specific memory T cell responses in the lung, but not protection against M. tuberculosis infection.